Comparison of Punishment Policies Against Children Narcotics Abuses in Indonesia and Thailand - Andika Dwi Amrianto; Indra Hafit Zahrulswendar (Universitas Muhammadiyah Yogyakarta, 2023)
The issue of narcotics is multifaceted and continues to evolve over time. According to data from the National Police and the National Narcotics Agency, a total of 3,281 children were found to be engaged in narcotics-related offenses in 2022. In 2015, Indonesia and Thailand became members of ASEAN, a regional organization committed to achieving a drug-free environment. Both countries collaborate to combat the illicit trafficking of narcotics and illegal drugs to ensure national and state security. In both Indonesia and Thailand, there is a concerning issue of narcotics abuse among children, who are considered the future leaders of their respective nations. This study aims to analyze the approaches taken by Indonesia and Thailand in criminalizing children involved in drug abuse. It also seeks to identify and compare the similarities and differences in their respective approaches towards addressing this issue. This study employed the normative juridical research method, specifically utilizing the comparative method of law. The comparative method involves analyzing the norms, doctrines, and rules that are applicable in both countries. Primary, secondary, and tertiary legal materials relevant to this research are utilized in this analysis. The obtained data was analyzed using descriptive qualitative analysis. The study revealed differences and similarities in factors such as the child's age, settlement of cases outside of court, types of crimes considered during sentencing, and court examination procedures.